PENYAJIAN ORGAN TUNGGAL DALAM PESTA PERKAWINAN DI NAGARI TALANG KOTO PULAI TAPAN KECAMATAN RANAH IV HULU TAPAN KABUPATEN PESISIR SELATAN - Hike Purwanti Wahyudani; Syeilendra Syeilendra; Yensharti Yensharti (SENDRATASIK UNP, 2014)
Abstract This study aimed to describe the presentation of a single organ at the wedding receptions in Nagari Talang Koto Pulai Tapan. The method used is descriptive qualitative research with human research instrument is an instrument. The study was conducted on February 15, 2014 in Nagari Talang Koto Pulai Tapan, Kabupaten Pesisir Selatan. The results of the study found that a single organ music presented on the third day after the marriage / wedding receptions. The place that used only a small stage that rested on the right, left, front of the house or if the yard of a house narrow the taking of the road. Presentation time during the day and at night. Presentation time daylight hours ranged from 9:00 a.m. to 17:00 am and evening hours ranging from 9:00 p.m. to 03:00 am. The singer who is a singer who has a stunningly good singers sound management provided by a single organ and a singer of songs in the show as diverse as pop, Minang, dangdut, kasidah. In the evening the songs presented are also an assortment of mixed again with dj, house and also Remik. Every single organ always presenting a rendition of 'Night bainai'. Attendance of a single organ music is a guest and family of parents, youth and children.   Kata kunci : Penyajian, Organ tunggal, Pesta Perkawinan